Single Source Precursor-based Solvothermal Synthesis of Heteroatom-doped Graphene and Its Energy Storage and Conversion Applications - Bo Quan; Seung-Ho Yu; Dong Young Chung; Aihua Jin; Ji Hyun Park; Yung-Eun Sung; Yuanzhe Piao (Scientific Reports)
Abstract Solvothermal processes are considered efficient approaches for the gram-scale production of graphene. Further modification of graphene by chemical doping is an important approach to tailor its properties. In this work, we successfully synthesized sulfur-doped graphene by using a solvothermal method with dimethyl sulfoxide as a precursor, which is a common laboratory reagent. Nitrogen-doped graphene was produced to demonstrate the generality of this process. These heteroatom-doped graphene materials exhibited high surface areas and high contents of heteroatoms. Furthermore, the lithium-ion storage properties and oxygen reduction reaction catalytic activity of these materials were also investigated. The success of this approach might facilitate the development of other advanced graphene-based materials with relative simplicity, scalability and cost effectiveness for use in various potential applications.